2023
DOI: 10.1002/cam4.5672
|View full text |Cite
|
Sign up to set email alerts
|

Do young adults with cancer receive information about treatment‐related impact on sex life? Results from a population‐based study

Abstract: Background Sexual dysfunction is common following a cancer diagnosis in young adulthood (18–39 years) and problems related to sex life are ranked among the core concerns in this age group. Yet, few studies have investigated to what extent adults younger than 40, receive information from healthcare providers about the potential impact of cancer and its treatment on their sex life. Methods A population‐based cross‐sectional survey study was conducted with 1010 young adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
(111 reference statements)
0
4
0
Order By: Relevance
“…This finding is aligned with results from a cross-sectional study ( N = 56) by Albers et al [ 36 ] who found that only 41% of AYAs did receive information about sexual health from a healthcare professional, and only 21% found the information satisfactory. Also, a nationwide population-based study ( N = 1010) by Bergström et al [ 38 ] reported that men to a higher extent than women reported having received information about the potential cancer-related impact on their sex life (68% vs. 54%, p < 0.001). The AYAs with cancer participating in our study provide suggestions for what and how to provide information about sexual health (see Table 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…This finding is aligned with results from a cross-sectional study ( N = 56) by Albers et al [ 36 ] who found that only 41% of AYAs did receive information about sexual health from a healthcare professional, and only 21% found the information satisfactory. Also, a nationwide population-based study ( N = 1010) by Bergström et al [ 38 ] reported that men to a higher extent than women reported having received information about the potential cancer-related impact on their sex life (68% vs. 54%, p < 0.001). The AYAs with cancer participating in our study provide suggestions for what and how to provide information about sexual health (see Table 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although not measuring awareness, discussions with HCPs about sexual problems as late effects have been associated with higher treatment intensity, male gender and HCP experience in studies of cancer survivor of all ages, not restricted to CAYACS. 14,43 Need for information about sexual problems as late effects was reported by about three times as many CAYACS (not including malignant melanomas) compared to the malignant melanoma group. Our findings align with previous studies reporting information needs among 15-50% of CAYACS of various cancers mainly in the first few years of survivorship, 16,[44][45][46][47] but provides novel insights that such needs persist decades beyond diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…12 Reporting sexual problems has been associated with increased treatment intensity, mental health issues, fatigue, and weight in CAYACS. [13][14][15][16][17] Addressing sexual problems is important as they are negatively associated with well-being and quality of life. [18][19][20][21] CAYACS experience more sexual problems than siblings or controls.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, testosterone deficiency and sexual health issues can manifest as long-term consequences of treatment. While many male patients are informed of the possible sexual health implications of treatment at diagnosis [ 3 ], there is a need for follow-up on the subject after cessation of lymphoma treatment [ [4] , [5] , [6] ].…”
Section: Introductionmentioning
confidence: 99%